Integrated marketing communications and social marketing. Issue 3 (13th July 2015) - Dahl, Stephan; Eagle, Lynne; Low, David
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the view of integrated marketing communications (IMC) by social marketing practitioners. Specifically, the paper furthers the discussion how a symbiotic relationship between IMC and social marketing can lead to both practical improvements of health-related social marketing campaigns, as well as theoretical advancement of the IMC construct. Design/methodology/approach – Based on semi-structured, in-depth interviews with practitioners, the authors provide exploratory evidence for support for IMC within the social marketing community and highlight potential differences and similarities when transferring IMC from a commercial to a social context. Findings – Three main differences emerged when transferring IMC from a commercial to a social context. These include differences of customer-centric approaches between commercial and social marketing, the need to weigh out the application of IMC to the charity brand or the use of IMC at a behavioural level and, finally, different complexity levels of desired behaviour as a mediating factor. Research limitations/implications – As with all qualitative data, the findings may not be generalisable beyond the interview participants and organisations studied. Practical implications – Many practitioners expressed that they liked IMC as a concept, but they lacked guidance as to the application with a social marketing context. This paper contributes to providing this guidance and establishing a body of knowledge how IMC can be applied in a non-commercial setting. Originality/value – The paper contributes to the practical development of guidance how the largely commercially applied IMC construct can be modified to be used in a social marketing context, while correspondingly highlighting how IMC needs to evolve to grow beyond purely commercial application.